Age of the Geek Depictions of Nerds and Geeks in Popular Media (Springer International Publishing, 2018)
This collection examines the nerd and/or geek stereotype in popular culture today. Utilizing the media-film, TV, YouTube, Twitter, fiction-that often defines daily lives, the contributors interrogate what it means to be labeled a "nerd" or "geek." While the nerd/geek that is so easily recognized now is assuredly a twenty-first century construct, an examination of the terms' history brings a greater understanding of their evolution. From sports to slasher films, Age of the Geek establishes a dialogue with texts as varied as the depictions of "nerd" or "geek" stereotypes.